Beamforming capability of a cross-slotted ring patch antenna array at 2.4 GHz wireless applications - Abdul Malek, Norun; Ali, Khamis; Jusoh, Ahmad Zamani; Mohamad, Sarah Yasmin; Zainal Abidin, Zuhairiah; Asnawi, Ani Liza (Institute of Electrical and Electronics Engineers Inc., 2018)
Microstrip patch antennas are widely used in modern day communication devices due to their light weight, low cost and ease of fabrication. In this paper, we have designed and fabricated a Cross-Slotted Ring Microstrip Patch Antenna and array at 2.4 GHz for Wireless Local Area Network (WLAN) applications using Computer Simulation Technology, CST. The designed antenna consists of rectangular radiating patch on Rogers RT5880 substrate and is excited by using coaxial probe feeding technique. The crossslotted ring has been designed on top of the radiating patch to improve bandwidth. The simulation and measurement results of the cross-slotted ring patch antenna are in close agreement with each other. The simulated and measured S-parameters shows -21dB and -15.6 dB at 2.4 GHz respectively. Then, the antenna has been formed into 1x4 array in order to observe its beamforming capability. The proposed antenna array is suitable for 802.11b/g/n Wi-Fi standard which is proposed to be used for IoT.